Blockchain-Based DLTs for Metaverse Applications Security - Danial Jamil; Muhammad Jamil; Muhammad Hassam (Engineering Science Letter, 2023)
Distributed Ledger Technologies (DLTs) and blockchain systems are used in various higher-level departments, government sectors and commercial industries. This article reviews how DLTs and blockchain systems work with IOT devices and how it provides security and scalability. The metaverse sets a new standard for social media sites and 3D virtual spaces. Moreover, the key aim of the virtual world is to safeguard the metadata of IOT customers. Additionally, crypto is an effective solution due to its openness, data integrity, and accountability characteristics. So, we review the two new burning technologies of crypto and the virtual world from a methodological perspective, i.e. data collection, saving data, allocation, integration, and data confidentiality are all aspects of data management. By each strategy, in this article, we discuss the methodological techniques of the meta chain and then investigate the potential benefits of blockchain technology. Further, we analyze how blockchain will influence other critical enabling technologies in the metaverse's service world, such as the IOT.